Tindakan Preventif dan Represif Non-Yustisial Penegakan Hukum Administrasi Oleh Eksekutif - Syahrul Machmud (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2017)
This study aims to determine the effectiveness of administrative environmental law enforcement by the executive. As it is known, enforcement of environmental law can be done through administrative law, civil law and criminal law. Administrative law is considered to have a strategic value that functions as an instrument of control, prevention and prevention of environmental pollution and / or damage. And administrative sanctions are intended so that violations can be stopped. Thus administrative sanctions become a juridical instrument that is both preventive (preventive) and at the same time repressive non-judicial (administrative sanctions imposed by the executive). This study uses a normative juridical method, and data collection is done through literature studies and document studies. From mass media, it can be seen that environmental pollution and / or destruction continues, this shows that the enforcement of administrative law by the executive has not run optimally. The Environment Supervisor (acting as a preventive measure) who is the spearhead of executive administrative law enforcement is very inadequate, this has an impact on the lack of repressive non-judicial actions (giving sanctions without going through a court). There are still too many weaknesses in the implementation level, so that the enforcement of administrative law by the executive must get serious improvement.